Apparent digestibility and ingestive behavior of Nellore bulls with low and high residual feed intake - Menezes, Rayanne Galdino; Fernandes, Juliano Jose de Resende; Di Calaca, Alana Maria Menezas; Arnhold, Emmanuel; Fernandes, Marcia Helena Machado da Rocha [UNESP]; Couto, Victor Rezende Moreira (Springer, 2022)
The objective of this study was to determine the correlation between ingestive behavior, apparent digestibility, and residual feed intake (RFI) of finishing Nellore bulls fed a high concentrate diet. One hundred and twenty Nellore bulls, housed in individual pens, were evaluated in individual performance tests. The animals were fed a high concentrate diet (23:77 roughage/concentrate ratio). The animals were classified as low RFI, medium RFI, and high RFI. Data from ten animals from each group were used. Fecal production and nutrient digestibility were calculated using indigestible neutral detergent fiber as an internal marker. The feeding behavior was evaluated over 24 h by direct observation every 5 min. The most efficient animals (low RFI, 8.58 kg DM/day) consumed 27.62% less feed than the least efficient animals (high RFI, 10.95 kg DM/day). Animals with medium efficiency (mean RFI, 9.49 kg DM/day) consumed 15.39% less than high RFI. Nutrient digestibility coefficients were similar except for ether extract (P < 0.03) which was 8% greater for the high-RFI animals. No effect was observed for ingestive behavior (P > 0.05). Animals spent, on average, 3 h 28 min feeding, 7 h 32 min ruminating, and 13 h 40 min in idle time. In the present study, ingestive behavior and dry matter digestibility were not responsible for between-animal variation in residual feed intake in Nellore bulls fed a high concentrate diet.
Keywords: Beef cattle; Ingestive behavior; Feed efficiency; Digestibility; RFI